2008
DOI: 10.3922/j.psns.2008.2.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of malnutrition and sensory-motor stimulation on auditory evoked potentials.

Abstract: There is evidence that the auditory evoked potential (AEP) is altered by malnutrition both in laboratory animals and in humans. The objective of the present study was to determine whether changes in the AEP caused by malnutrition could be reversed by nutritional rehabilitation and sensorymotor and environmental stimulation during hospitalization. Six children aged 5-33 months with severe malnutrition (kwashiorkor, marasmus and marasmic-kwashiorkor) were admitted to the Pediatric Ward of a University Hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Auditory skills are extremely important in the development of language and speech of individuals. The development of these skills depends on processes that involve complex nerve pathways that can be affected by environmental, social and pathological factors, as described in the literature (1,2,(4)(5)(6)8) In the national and international literature there are few studies (23)(24)(25) that relate to malnutrition and development of the auditory processing skills. However, studies have also found lower performance found in children with malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Auditory skills are extremely important in the development of language and speech of individuals. The development of these skills depends on processes that involve complex nerve pathways that can be affected by environmental, social and pathological factors, as described in the literature (1,2,(4)(5)(6)8) In the national and international literature there are few studies (23)(24)(25) that relate to malnutrition and development of the auditory processing skills. However, studies have also found lower performance found in children with malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies have focused on the anatomical and biochemical changes in the developing brain with malnutrition, few studies have assessed the physiological changes. Taking into account that the most used AEP reaches the level of the brainstem, studies involving higher paths and cortical areas are necessary, focusing on persistence of the effects of malnutrition on higher cortical activity with present and future consequences for development [12]. Our aim was to compare the effect of delayed versus early introduction of intravenous lipid in preterm on the biochemical parameters and on brain development by the cortical auditory evoked potential (CAEP) latency and amplitude.…”
Section: Introductionmentioning
confidence: 99%